Sustainable Water Management Strategies for Mitigating Pesticide Pollution in Urban and Agricultural Areas - Primus, Audrey; Siganul, Aimie Peace; Emalya, Nikita; Yusnar, Cut; Wijayanti, Yureana; Rubiyatno; Permana, Rega; Park, Sang Hyeok; Thakali, Ocean; Aina, Corry; Wahyuningsih, Ni Putu Sri; Commey, Nii Amarquaye (Civil and Sustainable Urban Engineering, 2025)
The indiscriminate use of pesticides in Malaysian agriculture poses serious risks to both human health and groundwater quality.This study aims to evaluate the extent of pesticide contamination in Malaysian groundwater, identify its major sources, and examine current mitigation efforts. The primary routes of contamination include direct application, soil leaching, and surface runoff, with over twenty pesticide compounds listed as priority hazardous substances, commonly linked to oil palm, rice, and vegetable farming. Residential and industrial activities also contribute to the pollutant load. Due to their long environmental persistence, pesticides threaten aquatic ecosystems through bioaccumulation and biomagnification and increase the risk of severe health issues, including neurological disorders, reproductive problems, and cancer. Regulatory controls such as exposure limits and monitoring programs have been implemented to manage these risks. This review concludes that while regulatory mechanisms exist, more robust and proactive approaches are needed to mitigate groundwater contamination. Future efforts should focus on expanding the adoption of sustainable farming practices, strengthening groundwater monitoring, and enhancing regulatory enforcement to ensure long-term environmental and public health protection.